TED TALK IN THE ESP CLASSROOM OF PHILOSOPHY STUDENTS - Svetlana Danilina; Viktoriia Shabunina (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
Using authentic materials in teaching ESP is part and parcel of communicative approach methodology. Unadapted materials bring the classroom closer to real-life language use and overall make language learning more meaningful and engaging for students. The needs analysis of Ukrainian students, which shows that many of them wish to continue their studies in English language universities abroad, makes the use of authentic materials particularly relevant, as they model the situations that students can potentially face in their future professional life. The presence of a vast array of authentic materials available today is both a challenge and a benefit for teachers, since they have to choose the ones which would meet their students' needs and expectations. Based on an ESP class taught to philosophy students, this article offers a suggestion on how to approach teaching presentation making skills and provides the practical outcome of using a TEDx talk in the ESP classroom. The featured talk, which focuses on today's perception of stoicism, was followed by some tasks to promote students' critical thinking and facilitate their future presentation planning, as well as by the students' own presentations in which they had to make use of the strategies discussed in class. Listening to the genuine presentation and using it as a model for presentations of their own follows the principles of CLIL (Content and Language Integrated Learning), which can benefit students by its explicit emphasis on the content and gives them a chance to acquire syntax, lexis, and discourse style skills as a by-product of content-oriented learning.